Duality of channel encoding and decoding—Part II: rate‐1 non‐binary convolutional codes†. Issue 5 (14th January 2016) - You, Qimin; Li, Yonghui; Liew, Soung Chang; Vucetic, Branka
Abstract: This is the second part of a series of papers on a revisit to the bidirectional Bahl–Cocke–Jelinek–Raviv (BCJR) soft‐in‐soft‐out maximum a posteriori probability (MAP) decoding algorithm. Part I revisited the BCJR MAP decoding algorithm for rate‐1 binary convolutional codes and proposed a linear complexity decoder using shift registers in the complex number field. Part II proposes a low complexity decoder for rate‐1 non‐binary convolutional codes that achieves the same error performance as the bidirectional BCJR soft‐in‐soft‐out MAP decoding algorithm. We observe an explicit relationship between the encoding and decoding of rate‐1 convolutional codes in G F ( q ). Based on this relationship, the BCJR forward and backward decoding are implemented by dual encoders using shift registers whose contents are vectors of complex numbers. The input to the dual encoders is the probability mass function of the received symbols, and the output of the dual encoders is the probability mass function of the information symbols. The bidirectional BCJR MAP decoding is implemented by linearly combining the shift register contents of the dual encoders for forward and backward decoding. The proposed decoder significantly reduces the computational complexity of the bidirectional BCJR MAP algorithm from exponential to linear with constraint length of convolutional codes. To further reduce complexity, fast Fourier transform is applied. Mathematical proofs and simulation results are provided to validate our proposed decoder. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In the second part of this series paper, we observe an explicit relationship between the encoding and decoding of rate‐1 convolutional codes in G F ( q ). Based on this, we propose a simple representation of Bahl–Cocke–Jelinek–Raviv soft‐insoft‐out maximum a posteriori probability (MAP) decoding algorithm for rate‐1 non‐binary convolutional codes where the decoding can be implemented by dual encoders using shift registers. It achieves the same error performance as the conventional Bahl–Cocke–Jelinek–Raviv MAP while significantly reduces the computational complexity of the MAP algorithm from exponential to linear.